Modification of Growth, Yield, and the Nutraceutical and Antioxidative Potential of Soybean Through the Use of Synthetic Biostimulants - Szparaga, Agnieszka; Kocira, Sławomir; Kocira, Anna; Czerwińska, Ewa; Świeca, Michał; Lorencowicz, Edmund; Kornas, Rafał; Koszel, Milan; Oniszczuk, Tomasz (Frontiers in Plant Science, 2018)
Improvement of crop cultivation technologies is focused on increasing crop productivity and improving yield quality, and at the same time on minimizing risks posed to the natural environment. The use of biostimulants contributes to plants productivity increase, especially under their exposure to stress induced by negative environmental stimuli. A field experiment was conducted in three growing seasons (2014-2016). Seeds of soybean of Atlanta cultivar were sown in the third decade of April. Two synthetic biostimulants were used in the growing period in the form of a single (stage BBCH 13-15) or double spraying (stage BBCH 13-15, BBCH 61): Atonik (in concentrations of 0.1% and 0.2%) and Tytanit (in concentrations of 0.07% and 0.13%). The first tested biostimulant contained three phenolic compounds: sodium p-nitrophenolate, sodium o-nitrophenolate, and sodium 5-nitroguaiacolate. In turn, Tytanit preparation contained a titanium complex, magnesium oxide, and sulfur (VI) oxide. This works presents a complex study addressing the action of Atonik and Tytanit biostimulants and demonstrates their effect on the physiological traits, plant productivity and seed yield quality of Glycine max L. The conducted experiment proved that biostimulant type, as well as the number of its applications and its concentration modified the biometric traits, crop productivity, as well as yield quality and the nutraceutical and antioxidative potential of soybean seeds. It was also found that by positively affecting the plant growth and seed yield the Atonik and Tytanit biostimulants decreased contents of protein and lipids in seeds. The double application of these preparations in their higher concentrations had a more positive impact on soybean seed number and soybean seed yield. The use of both Atonik and Tytanit resulted also in an increased antioxidative activity of soybean seeds. The greatest increase in this activity was observed after the application of Tytanit preparation. Dietary fiber fraction analysis demonstrated an increase in contents of acid-detergent fiber, lignin and cellulose in soybean seeds as a result of biostimulants application, which was however greater upon the use of Tytanit. In contrast, contents of neutral-detergent fiber, cellulose and hemicellulose were observed to decrease in all analyzed combinations of crops treated with the tested preparations.